1986
DOI: 10.1002/lary.1986.96.11.1283
|View full text |Cite
|
Sign up to set email alerts
|

Small Cell Carcinoma of the Larynx: Results of Therapy

Abstract: Primary small cell carcinoma of the larynx is a rare malignancy with a dismal prognosis. A survey of the long‐term follow‐up from reported cases of small cell carcinoma of the larynx and a review of the recent experience with this tumor at the University of Michigan Hospitals was undertaken to determine if newer treatment approaches incorporating adjuvant chemotherapy were associated with prolonged survival. Median survival for those patients receiving adjuvant chemotherapy was 19 months compared to 11 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
2
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 29 publications
(2 reference statements)
0
55
2
2
Order By: Relevance
“…The most common sites of spread are cervical lymph nodes, liver, lung and bone [32]. In contrast to small cell lung cancer, only 8% of this tumor of the larynx metastasize to the central nervous system and then only as a preterminal event [33]. Many patients (about half) have cervical metastases on initial presentation [4] and the tumor should be considered as a disseminated disease at presentation [11].…”
mentioning
confidence: 99%
“…The most common sites of spread are cervical lymph nodes, liver, lung and bone [32]. In contrast to small cell lung cancer, only 8% of this tumor of the larynx metastasize to the central nervous system and then only as a preterminal event [33]. Many patients (about half) have cervical metastases on initial presentation [4] and the tumor should be considered as a disseminated disease at presentation [11].…”
mentioning
confidence: 99%
“…[12] A combination of platinum-based chemotherapy and radiotherapy is the mainstay of the treatment of SCNC, which is a systemic disease. [13] In the study by Baugh et al [14], the median survival of patients with laryngeal SCNC was reported to be up to 55 months following a definitive radiotherapy and adjuvant chemotherapy, which was significantly longer compared with other regimens (p=0.02). [14] In a meta-analysis, van der Laan et al also demonstrated that a combination of chemotherapy and radiotherapy had a higher five-year disease-specific survival (DSS) rate than those of other modalities (30.8% vs 12.9%; p=0.001).…”
Section: Discussionmentioning
confidence: 97%
“…[13] In the study by Baugh et al [14], the median survival of patients with laryngeal SCNC was reported to be up to 55 months following a definitive radiotherapy and adjuvant chemotherapy, which was significantly longer compared with other regimens (p=0.02). [14] In a meta-analysis, van der Laan et al also demonstrated that a combination of chemotherapy and radiotherapy had a higher five-year disease-specific survival (DSS) rate than those of other modalities (30.8% vs 12.9%; p=0.001). [13] In the aforementioned study, of the 436 laryngeal neuroendocrine cases; 183 were SCNC, 57.9% were located in the supraglottic area, while 66.7% were metastatic.…”
Section: Discussionmentioning
confidence: 97%
“…At the present time, therapeutic irradiation to the larynx and neck and adjuvant chemotherapy offer the least disabling and most effective form of therapy for patients with advanced forms (stage II-IV) of this highly aggressive cancer [11], The relatively short interval be tween onset of symptoms, detection of laryngeal disease and development of distant métastasés suggests that in most instances any treatment plan aimed exclusively at the laryngeal primary and neck is unlikely to signifi cantly influence the overall disease process.…”
Section: Management O F Small Cell Neuroendocrine Carcinomamentioning
confidence: 99%
“…As a result of its aggressive nature, small cell neuroen docrine carcinoma of the larynx should be considered disseminated at initial presentation [10][11][12], A thorough metastatic workup is therefore indicated. This could include a comprehensive history and physical examina tion, endoscopic evaluation of the upper aerodigestive tract, cytological examination of bronchial washings, bone marrow biopsy, computed tomography of the lungs, radionucleotide scanning of the bone and liver and imaging of the brain.…”
Section: Management O F Small Cell Neuroendocrine Carcinomamentioning
confidence: 99%